2017
DOI: 10.12693/aphyspola.132.742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Press Ram Pulsation on Deep Drawability of Dual Phase Steel Sheet

Abstract: A study of the influences of press ram pulsation on deep drawability of dual phase steel sheet is presented. General characteristics of deep drawing process, press ram pulsation technique and dual phase steels are briefly discussed. A finite element model is used to evaluate the influence of pulse motion profile of press ram on the thickness reduction of steel sheet and forming load. Commercial finite element software package DEFORM-3D is used for modelling and simulation of cylindrical cup drawing. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…After comparing various friction coefficients and making calculations using DEFORM, they concluded that the quality of circular cup formation decreased in the corners as the friction increased, resulting in thin areas or breakage. Olguner and Bozdana, in 2017, planned three sets of servo motion curves (frequency = 5, 10, and 20 Hz) for circular cup drawing and compared them with a conventional curve [8]. According to results obtained again using DEFORM, the punch force required for drawing decreased as the pulse frequency was increased, and when the motion curve was limited to the drawing of the circular cup, the formability of the circular cup was enhanced, and the chance of breakage was reduced.…”
Section: Strengths Weaknesses Traditional Methodsmentioning
confidence: 99%
“…After comparing various friction coefficients and making calculations using DEFORM, they concluded that the quality of circular cup formation decreased in the corners as the friction increased, resulting in thin areas or breakage. Olguner and Bozdana, in 2017, planned three sets of servo motion curves (frequency = 5, 10, and 20 Hz) for circular cup drawing and compared them with a conventional curve [8]. According to results obtained again using DEFORM, the punch force required for drawing decreased as the pulse frequency was increased, and when the motion curve was limited to the drawing of the circular cup, the formability of the circular cup was enhanced, and the chance of breakage was reduced.…”
Section: Strengths Weaknesses Traditional Methodsmentioning
confidence: 99%
“…The experimental design method could effectively optimize the pressure distribution required for the forming process of continuously variable pulleys and spur gears. Olguner and Bozdana [19] proposed a finite element model for a dual-phase steel plate to evaluate the reduction of steel plate thickness and the change of forming load in the pulse pressure distribution curve during the drawing process. They also changed the frequency and amplitude of the pulse pressure to perform elastoplastic FEA with DEFORM-3D.…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that the brittleness increased as the strength increased and that not only transverse, but also longitudinal cracks were seen in the DP800 and higher grades of steel. Olguner et al [16] investigated the effect of press ram pulsation amplitudes on the deep drawability of dual phase steel sheet using frequencies of 5, 10, and 20 Hz. They reported that their proposed method had a significant effect both in terms of thickness reduction and drawing force compared to conventional ram presses.…”
Section: Introductionmentioning
confidence: 99%